DESIGN AND APPLICATION OF MOTION CAPTURE ON 3D CHARACTERS IN VIDEO - Jimmy Pratama; Frenky Frenky (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Design and Application of Motion Capture on 3D Characters in Video. Motion Capture is a technology that can record the movement of a human model into a 2D or 3D digital realistically. In Indonesia itself, users of Motion Capture technology are still low in demand, the factor cost is very expensive and the availability of the Motion Capture system is limited. Over time, Mocap technology has been found which is simpler and easier to use by the general using the Kinect camera, which allows us to produce information depth, texture, user, and skeleton. The research method of this 3D animation video uses the MDLC (Multimedia Development Life Cycle). This animated video was made using the Mocap Markerless technique and the Blender 2.79b application as a media for making 3D characters up to the 3D animation stage. The design and implementation of Motion Capture on 3D characters in this video aims to prove and can help Mocap users understand how to design and implement simple Motion Capture creations on 3D characters into videos